Pengaruh Kompensasi, Motivasi, dan Konflik Terhadap Kinerja Karyawan BUMN Karya Kontruksi dengan Efisiensi Anggaran Pemerintah Variabel Moderasi - Abdul Dinata Destra; Luis Marnisah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of compensation, motivation, and work conflict on employee performance in a state-owned construction company, with government budget efficiency as a moderating variable. The research phenomenon stems from the suboptimal performance of employees in government infrastructure projects due to compensation discrepancies, low motivation, and internal conflict amidst demands for efficient use of the state budget. The study used a quantitative approach with multiple linear regression analysis and moderated regression analysis (MRA). The study population consisted of 60 employees using a saturated sampling technique. Data were obtained through a Likert-scale questionnaire and processed using SPSS version 25, accompanied by validity, reliability, and classical assumption tests to ensure data quality. The results of the partial test (t-test) showed that compensation and motivation had a significant positive effect on employee performance. The results of the simultaneous test (F-test) proved that compensation, motivation, and work conflict together had a significant effect on employee performance. Simultaneously, all independent variables had a significant effect on performance. The variable of government budget efficiency was shown to moderate the relationship between compensation and motivation on performance, but did not moderate the relationship between work conflict and performance. These findings indicate that budget efficiency can strengthen the positive influence of compensation and motivation on performance improvement, but is not yet effective in reducing the negative impact of work conflict. The research findings are expected to serve as a reference for the management of state-owned construction companies (BUMN Karya Konstruksi) in formulating human resource management strategies that balance budget efficiency with improving employee welfare to achieve optimal organizational performance.